2020
DOI: 10.3389/fimmu.2020.567210
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells in Pediatric Hematopoietic Cell Transplantation a Review and a Pilot Study in Children Treated With Decidua Stromal Cells for Acute Graft-versus-Host Disease

Abstract: Mesenchymal stromal cells (MSCs) are rare precursors in all organs of the body. MSCs have profound anti-inflammatory effects and reduce alloreactivity in vitro and in vivo. In pediatric allogeneic hematopoietic cell transplantation (HCT), MSCs have mainly been used to treat acute graft-versus-host disease (GVHD). MSCs are commercially available for this indication in Canada, Japan, and New Zeeland. More rare indications for MSCs in pediatric patients include graft failure and chronic GVHD. MSCs from bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 125 publications
1
10
0
1
Order By: Relevance
“…DSCs were used to treat six pediatric patients with severe acute GvHD, grade III-IV and all six responded (118). Unfortunately, one of the patients, a teenage boy with Sickle Cell Disease (SS) died of severe brain hemorrhages a few months post HCT, but at time of HCT, he had severe sequelae due to untreated SS.…”
Section: Treatment Of Acute Gvhdmentioning
confidence: 99%
See 1 more Smart Citation
“…DSCs were used to treat six pediatric patients with severe acute GvHD, grade III-IV and all six responded (118). Unfortunately, one of the patients, a teenage boy with Sickle Cell Disease (SS) died of severe brain hemorrhages a few months post HCT, but at time of HCT, he had severe sequelae due to untreated SS.…”
Section: Treatment Of Acute Gvhdmentioning
confidence: 99%
“…Overall, these data indicate partial effectiveness of MSCs and DSCs particularly in the treatment of severe acute GvHD in children with room for improvement. Our experience regarding DSCs in the pediatric population is limited, and further studies are needed (118). The outcome with DSCs in adults with acute GvHD is most promising (34,46,119).…”
Section: Treatment Of Acute Gvhdmentioning
confidence: 99%
“…GvHD in the treatment of six children with decidual stromal cells (DSCs). Further, MSCs derived from different tissues are well-tolerated and have shown promising outcomes for acute GvHD in patients [61].…”
Section: Ringdén Et Al Demonstrated That Co-transplantation Of Hct An...mentioning
confidence: 99%
“…Some recent studies have used MSC-EVs, because of their additional benefits, for cellular therapy in allo-HSC grafts, engraftment, and inhibition of GvHD. Application of MSC-EVs improved the effects of HSCs, including enhancing selfrenewal, inhibiting differentiation, promoting homing for HSC expansion, and preventing GvHD following HSCT [69].…”
Section: Mscs Transduced With Il-10 or Through Exposure To Ifn-γ And ...mentioning
confidence: 99%
“…In a pilot study, six children were treated with decidua stromal cells (DSCs) for steroid refractory aGVHD. A complete response was observed in four children, and a partial response was observed in two children at 6 months [ 122 ]. A meta-analysis showed that infusion of MSCs prevents GvHD.…”
Section: Prophylaxis and Treatment Of Gi Gvhd After Hsctmentioning
confidence: 99%